Academic Self Concept of Physical Education Students - Yahya Eko Nopiyanto; Yarmani; Ari Sutisyana; Syafrial; Arwin; Tono Sugihartono (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Knowing the level of student academic self concept is the main goal in this research. The research design used is a survey with a quantitative descriptive method. The population involved in this study was 50 students. The sample used in this study was 50 students using total sampling. The instrument in the form of a questionnaire was used to collect research data. The mean ideal and the standard deviation ideal were used to analyze the research data. The results of the analysis show that: 1) the mean value of male students is 61.8 and the standard deviation of 13.61; 2) the mean value of female students of 31.3 and the standard deviation of 11.90. So, it can be concluded that the level of academic self-concept of physical education students is in the high category.